Functional responses of human and rabbit platelets induced by milk from indigenous Greek dairy goats (Capra prisca) - Dimitrios Peschos, Yannis Simos, George Fthenakis, John Zelovitis, Athina Boulaka, Maria Giouli, Elena Georgiou, Vasilios Ragos, Athina Tzora, George Tsangaris, Angelos Evangelou, Spyridon Karkabounas (Journal of Applied Pharmaceutical Science, 2016)
The aim of this study was to investigate the biological properties of goat milk from the indigenous Greek breed (Capra prisca). The activity of the milk on platelet aggregation and thromboxane B2 (TXB2) production was evaluated on platelets isolated from blood obtained from both humans and rabbits. To further understand the biological properties of the milk ascorbic acid, linoleic and linolenic acid, were also tested. Ex vivo trials showed that milk from indigenous Greek dairy goats (Capra prisca) inhibited platelet aggregation at a dose dependent manner, both in humans and rabbits and decreased production of TXB2. The milk’s ability to inhibit platelet aggregation and reduce TXB2 production could be attributed to its high content in antioxidant substances and poly-unsaturated fatty acids (such as ascorbic acid and linolenic acid), when originating from grazing goats in semi-mountainous shrublands. The paper provides information for nutritionists and health professionals, about the biological properties of specific types of milk and their potential use as functional foods.
Keywords: Goats’ milk, platelets, thromboxane, ascorbic acid, linolenic acid.